Reaksi Pasar Modal Sebelum Dan Sesudah Munculnya Financial Technology (Fintech) Peer To Peer (P2P) Lending Pada Bank Yang Terdaftar Di Bursa Efek Indonesia - Febriyanto, Febriyanto; Ali, Karnila; Raniana, Vina (Jurnal Manajemen DIVERSIFIKASI, 2023)
The development of innovation in the financial sector, namely fintech, fintech is an abbreviation of financial technology or financial technology. The existence of financial technology has made one of the fastest growing business sectors in the technology sector. With the development of technology and the increase in start-up companies, the development of fintech in Indonesia. Finance in Indonesia has shifted due to a format that can produce solutions and make it easier for consumers, namely the combination of economy and technology (fintech). The purpose of this study is to determine whether there are differences in trading volume activity and abnormal returns on the cooperation between banks listed on the Indonesia Stock Exchange and peer to peer P2P lending financial technology. This study uses secondary data from third-party publications with a total sample of 4 companies. The data analysis technique used is the even study data analysis, normality test and paired t-test hypothesis testing. Based on the research results, there is no significant difference in the volume of stock trading activity (trading volume activity) before and after the collaboration between peer to peer lending financial technology and banks listed on the Indonesia Stock Exchange, there is no significant difference in abnormal returns before and after the existence of cooperation between financial technology peer to peer lending to banks listed on the Indonesia Stock Exchange.